2011
DOI: 10.3892/mmr.2011.609
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylated T567 ezrin is associated with merlin expression in KIT-mutant gastrointestinal stromal tumors

Abstract: Abstract. Membrane-cytoskeleton linker organizer ezrin is a member of the ERM (ezrin-radixin-moesin) protein family. It has been suggested as an important element in the oncogenic process, particularly in conferring a metastatic ability on tumor cells. We hypothesized that the KIT oncogenic form is one of the proteins that modulates expression of the ezrin protein via phosphorylated ezrin at different residues; furthermore, it may interact with the protein merlin, and promoting tumor development via the PI3K o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Interestingly, Zawawi et al[ 45 ] previously reported that the blockade of moesin function inhibited the LPS-induced activation of MyD88, IRAK and TRAF6, as well as subsequent MAPK activation and NF-κB translocation to the nucleus. Weng et al [ 47 ] also confirmed that the phosphorylation of ezrin triggered MAPK signal transduction in tumor progression. Thus, our results are consistent with a specific role for the ERM family in the activation of p38 and NF-κB activation.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, Zawawi et al[ 45 ] previously reported that the blockade of moesin function inhibited the LPS-induced activation of MyD88, IRAK and TRAF6, as well as subsequent MAPK activation and NF-κB translocation to the nucleus. Weng et al [ 47 ] also confirmed that the phosphorylation of ezrin triggered MAPK signal transduction in tumor progression. Thus, our results are consistent with a specific role for the ERM family in the activation of p38 and NF-κB activation.…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, Zawawi et al [16] previously reported that the blockade of moesin function inhibited the LPS-induced activation of MyD88, IRAK and TRAF6, as well as subsequent MAPK activation and NF-κB translocation to the nucleus. Weng et al [37] also con rmed that the phosphorylation of ezrin triggered MAPK signal transduction in tumor progression. Thus, our results are consistent with a speci c role for the ERMs family in the activation of p38 and NF-κB activation.…”
Section: Discussionmentioning
confidence: 93%
“…Inhibiting ezrin function in these transformed cells abolishes fos-mediated membrane ruffling and cell motility [7]. Furthermore, GIST harbors a mutation in the KIT oncogene that activates ezrin at different residues to promote tumor progression [111]. …”
Section: Ezrin Activation and Role In Biologymentioning
confidence: 99%